2003
DOI: 10.2135/cropsci2003.1283
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cry1Ab Protein and Hybrid Genotype on Fumonisin Contamination and Fusarium Ear Rot of Corn

Abstract: corn (Cawood et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 42 publications
3
40
0
3
Order By: Relevance
“…The MON 810 event encodes for a Cry1Ab protein which is an δ-endotoxin highly toxic to lepidopteran larvae. However, Clements et al (2003) observed that the Cry1Ab protein was associated with reduced fumonisin concentration in grain when O. nubilalis was the predominant insect pest but not when Helicoverpa zea (Boddie) was the prevalent one. The susceptibility of the insect species to the proteins had to be taken into consideration because it impacted the mycotoxin levels.…”
Section: Resultsmentioning
confidence: 98%
“…The MON 810 event encodes for a Cry1Ab protein which is an δ-endotoxin highly toxic to lepidopteran larvae. However, Clements et al (2003) observed that the Cry1Ab protein was associated with reduced fumonisin concentration in grain when O. nubilalis was the predominant insect pest but not when Helicoverpa zea (Boddie) was the prevalent one. The susceptibility of the insect species to the proteins had to be taken into consideration because it impacted the mycotoxin levels.…”
Section: Resultsmentioning
confidence: 98%
“…Nevertheless, it ended up in corn chips and other food products, which had to be recalled. A possible health benefit of other Bt corn is lower levels of mycotoxin in regions where damage from the eastern corn borer is extensive (e.g., Clements et al 2003). Hallerman (2002) and, where applicable, ISB (2004a).…”
Section: Box 2 Food Plants With Transgenic Resistance Traitsmentioning
confidence: 99%
“…Another benefit from the use of Bt corn has been the well-documented reductions in mycotoxin contamination that sometimes occur. Reductions in both fumonisins and aflatoxins have been reported in field studies on several continents [111][112][113][114][115]. These reductions have been associated with reduced insect wounding on kernels expressing a Cry endotoxin, resulting in fewer openings for infection by mycotoxin-producing fungi [114,116].…”
Section: Reducing Infection Courtsmentioning
confidence: 99%